PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PADA WARGA BELAJAR PROGRAM PAKET C MATA PELAJARAN SOSIOLOGI DI PKBM AULIA JAKARTA UTARA - Yu, Riska (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2023)
By applying the jigsaw type of cooperative learning model to citizens studying the package C program at PKBM Aulia North Jakarta, this study aims to find out the steps for implementing this model and collect data regarding sociology learning outcomes on the impact of social change. The jigsaw cooperative learning model is a learning model that is focused on learning citizens to interact with each other in small groups. This study utilizes the pre-trial technique because there are external factors that influence the dependent variable as the main data source for researchers. One-group pretest-posttest design is utilized in the pre-experimental research method. Researchers use this technique because the results of the examination can be known precisely and can be adjusted to the conditions before and after being given treatment. Observation and tests pretest-posttest were the instruments used in this study. The average score on the pretest was 29.62 and the average score on the posttest was 96.54 an increase of 66.92. after that the difficulty test was taken and the results showed that six questions in the medium category and four questions in the difficult category. The result of the pretest and posttest show that the jigsaw cooperative learning model has potential to improve learning outcomes of learning citizens. The testing of the application of the jigsaw cooperative learning model to improve learning outcomes for residents learning the package C program at PKBM Aulia North Jakarta was successful in achieving its intended results. Keywords: Learning Outcomes, Jigsaw Cooperatif Learning Model